2019
DOI: 10.1002/jcp.28865
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: A new inhibitor agent for cervical cancer treatment

Abstract: Cervical cancer is one of the most common cancers between women and is known as the third leading cause of female cancer related deaths annually. Its detection in early stages allows it to be a preventable and generally treatable disease. Increasing evidence revealed, a variety of internal and external factors are associated with initiation and progression of cervical cancer pathogenesis. Human papilloma virus infection is found as a major cause of cervical cancer. Other molecular and biochemical alterations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 138 publications
(137 reference statements)
0
45
0
Order By: Relevance
“…Cervical cancer is known as the fourth cancer among women and the eighth common cancer worldwide [1,2]. Cervical cancer is a result of being infected by some types of human papillomavirus or HPV, which are effective on the mucosa [3,4]. Findings indicated that HPV is a necessary cause of cervical cancer; this means that the other risk factors can increase the risk of cervical cancer, but they are not able to develop this kind of cancer in the absence of HPV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is known as the fourth cancer among women and the eighth common cancer worldwide [1,2]. Cervical cancer is a result of being infected by some types of human papillomavirus or HPV, which are effective on the mucosa [3,4]. Findings indicated that HPV is a necessary cause of cervical cancer; this means that the other risk factors can increase the risk of cervical cancer, but they are not able to develop this kind of cancer in the absence of HPV [5].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin exhibits anticancer features through many functions including inhibition of fatty acids and growth factor uptake by tumor cells, suppression of the activity of telomerase (via decreasing the length of telomere), induction of apoptosis, inhibition of endothelin‐1 synthesis (which is an angiogenic factor), increased growth of blood vessels, and regulation of some tumor suppressors’ expression, such as TP53 . A large number of in vitro and in vivo studies have confirmed the antitumor properties of melatonin . In the rat model, it was observed that melatonin at physiological concentrations could suppress the primary phase of carcinogenesis .…”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%
“…69,70 A large number of in vitro and in vivo studies have confirmed the antitumor properties of melatonin. 15,71 In the rat model, it was observed that melatonin at physiological concentrations could suppress the primary phase of carcinogenesis. 72 Melatonin suppresses DNA damage and alterations such as mutations and amplifications resulting from carcinogens and thereby inhibit neoplastic transformation.…”
Section: Anticancer Features Of Melatoninmentioning
confidence: 99%
See 2 more Smart Citations